Programi, namenjeni starševstvu, kot pomemben člen promocije duševnega zdravja - Grmek, Helena (Revija za zdravstvene vede, 2023)
The purpose of the paper is to present the importance and effectiveness of various counse-ling programs for parents as a potential for the pro-motion of mental health and the strengthening of pu-blic health in the Republic of Slovenia. There are so many programs worldwide. However, they all share a common purpose. This includes improving populati-on health, improving well-being, and helping parents manage potentially problematic behaviors in chil-dren. We examined the literature in a variety of data-bases: Medline PubMed, BioMed Central, ProQuest, COBISS, Google Scholar. In the paper, we presented various programs and evidence of their effectiveness. The integration of parental counseling programs in the public health system can be understood as an effective contribution to the implementation of the broader concept of health education.
Keywords: early childhood; javno zdravje; parenting-oriented counseling programs; public health; starši; svetovalni programi; zgodnje otroštvo